2005
DOI: 10.1128/aac.49.7.2677-2686.2005
|View full text |Cite
|
Sign up to set email alerts
|

Alteration of Fatty Acid and Sterol Metabolism in Miltefosine-Resistant Leishmania donovani Promastigotes and Consequences for Drug-Membrane Interactions

Abstract: Miltefosine (hexadecylphosphocholine [HePC]) is the first orally active drug approved for the treatment of visceral leishmaniasis. In order to investigate the biochemical modifications occurring in HePC-resistant (HePC-R) Leishmania donovani promastigotes, taking into account the lipid nature of HePC, we investigated their fatty acid and sterol metabolisms. We found that the content of unsaturated phospholipid alkyl chains was lower in HePC-R parasite plasma membranes than in those of the wild type, suggesting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
113
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(132 citation statements)
references
References 34 publications
8
113
0
11
Order By: Relevance
“…MTF is an alkylphosphocholine that mainly interferes with alkyl-lipid metabolism, phospholipid biosynthesis, and membrane composition and fluidity in Leishmania (49-51). Moreover, modification of lipid membrane content has been described in MTF-resistant lines (52). We found two genes, on cosmids LinJ.29b (LinJ.29.2250) and LinJ.…”
Section: High-throughput Screening Of the Five Major Antileishmanial mentioning
confidence: 83%
See 1 more Smart Citation
“…MTF is an alkylphosphocholine that mainly interferes with alkyl-lipid metabolism, phospholipid biosynthesis, and membrane composition and fluidity in Leishmania (49-51). Moreover, modification of lipid membrane content has been described in MTF-resistant lines (52). We found two genes, on cosmids LinJ.29b (LinJ.29.2250) and LinJ.…”
Section: High-throughput Screening Of the Five Major Antileishmanial mentioning
confidence: 83%
“…Cos-Seq nonetheless allows detection of indirect resistance mechanisms resulting from drug transport alterations. For example, modification of membrane lipid content has been described in MTF-resistant lines (52), and the two genes characterized in the MTF Cos-Seq screen, which pertain to ergosterol biosynthesis and phospholipid translocation, might well trigger MTF resistance via membrane fluidity/ permeability changes.…”
Section: Discussionmentioning
confidence: 99%
“…In laboratory studies it was observed that in wild-type promastigotes of Leishmania donovani, miltefosine is able to induce a cell death process with numerous cytoplasmic, nuclear, and membrane features of metazoan apoptosis, including cell shrinkage, DNA fragmentation into oligonucleosome-sized fragments, and phosphatidylserine exposure. The activity of miltefosine is attributed to interaction with cell signal transduction pathways and inhibition of phospholipids and sterol biosynthesis [4]. Miltefosine does not appear to kill L.donovani promastigotes by direct toxic mechanism.…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Since biological membranes are composed of dynamically condensed domains surrounded by fluid domains, it has been suggested that, above the CMC, alkylphospholipids can insert into both kinds of phases: as monomers into the condensed phase and as a group of monomers into the fluid phase. (Rakotomanga et al, 2005). The presence of albumin in the medium has the effect of increasing the CMC value by binding molecules of lipids and, hence, reducing the concentration of free monomers in the medium (Kim et al, 2007).…”
Section: Transport Of Spin Labeled Perifosine (Opp) From Liposomes Tomentioning
confidence: 99%